Ultrasensitive RNase H activity detection using the transcription-based hybrid probe and CRISPR/cas12a signal amplifier - Ding, Sheng; Wei, Yinghua; Yang, Minglong; Shi, Jinyi; Ren, Kaiyuan; Li, Xinli; Tang, Zhuo (Frontiers in Pharmacology, 2025)
Ribonuclease H (RNase H), a critical functional protein in replication and genome stability, is emerging as a crucial therapeutic target for various diseases, including immune disorders. We present a transcription-based hybrid probe, referred to as Hybprobe, and a CRISPR/Cas12a signal amplifier for the rapid, sensitive, and low-cost detection of RNase H activity. In this method, the RNA strand of the Hybprobe is specifically cleaved by RNase H, releasing a single-stranded DNA activator that facilitates recognition and cleavage by the Cas12a/crRNA complex, triggering signal amplification via Cas12a′s trans-cleavage activity. The proposed method demonstrates ultra-high sensitivity, capable of detecting RNase H as low as 9.02 × 10−10 U/μL, making it approximately 1,000 times more sensitive than several previously reported methods. Furthermore, we demonstrated the application of this method for RNase H inhibitor evaluation and its practical use across various biological samples, including cell extracts and HIV reverse transcriptase. In summary, the results suggest that this method is a promising tool for the highly sensitive detection of RNase H and the diagnosis of diseases associated with RNase H.